PATIENTS WITH PSYCHOTIC DISORDERS RECOGNIZE FACIAL EMOTIONAL EXPRESSION BETTER IN EMOTIONS COMPARED TO IN IMAGES: Life Sciences-Neurobiology - M.D, PARTAM MANALAI; MANALAI, GUL G.; MYINT M.D., KHIN; ATA M.D, PASHMINA; HARACIC, ASIM (International Journal of Life Science and Pharma Research, 2012)
One of the well-documented findings in patients with schizophrenia is the deficit in processing facial expressions of emotional states. It is, however, unclear whether these patients are deficient in interpreting the intensity of facial expression or the emotional states altogether. In the current study we examine the ability of patients with a diagnosis of schizophrenia or schizoaffective disorder to identify the facial expression in emoticons and pictures of common emotional expressions. We recruited 10 normal individuals and 20 patients with diagnoses of schizophrenia and schizoaffective disorders. Individuals were presented with pictures of emotional states and emoticons along with a list of emotions to be matched to the image and emoticons. The patients suffering from schizophrenia and schizoaffective disorders were able to correctly identify emotional expression in emoticons significantly better than in images (91.7% vs 73%, p=0.0001, Fisher’s exact test). To our knowledge this is the first study to evaluate the ability of patients with severe psychotic disorders to differentiate between gross and subtle facial changes during expression of emotional states using emoticons. Our findings suggest that patients suffering from schizophrenia and schizoaffective disorders may have difficulty understanding the subtle facial expression of emotions with relative preservation of ability to recognize the stereotypical features of facial emotional expressions. Further research is needed to validate these findings.